Answer:
24/36 or simplified 2/3 of a yard
Step-by-step explanation:
Answer: 6
Step-byStep:
[(18- 8) x 3) + (4+3) x 6] divided by 12
step 1- start with the stuff in the parentheses
[(10 x 3) + (7 x 6)] divided by 12
step 2- simplify things in parentheses
[30 + 42] divided by 12
step 3- simplify even more
[72] divided by 12
step 4- remove brackets, and simply even further
72 divided by 12 = 6
Hope this helps
Answer:
![(fof^{-1})(x)=x](https://tex.z-dn.net/?f=%28fof%5E%7B-1%7D%29%28x%29%3Dx)
Step-by-step explanation:
Composition of two functions f(x) and g(x) is represented by,
(fog)(x) = f[g(x)]
If a function is,
f(x) = (-6x - 8)² [where x ≤
]
Another function is the inverse of f(x),
![f^{-1}(x)=-\frac{\sqrt{x}+8}{6}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D-%5Cfrac%7B%5Csqrt%7Bx%7D%2B8%7D%7B6%7D)
Now composite function of these functions will be,
![(fof^{-1})(x)=f[f^{-1}(x)]](https://tex.z-dn.net/?f=%28fof%5E%7B-1%7D%29%28x%29%3Df%5Bf%5E%7B-1%7D%28x%29%5D)
= ![[-6(\frac{\sqrt{x}+8}{6})-8]^{2}](https://tex.z-dn.net/?f=%5B-6%28%5Cfrac%7B%5Csqrt%7Bx%7D%2B8%7D%7B6%7D%29-8%5D%5E%7B2%7D)
= ![[-\sqrt{x}+8-8]^2](https://tex.z-dn.net/?f=%5B-%5Csqrt%7Bx%7D%2B8-8%5D%5E2)
= ![(-\sqrt{x})^2](https://tex.z-dn.net/?f=%28-%5Csqrt%7Bx%7D%29%5E2)
= x
Therefore, ![(fof^{-1})(x)=x](https://tex.z-dn.net/?f=%28fof%5E%7B-1%7D%29%28x%29%3Dx)
Answer:
2x + 3y - 24 = 0
Step-by-step explanation:
2x + 3y = 18
3y = -2x + 18
y =
x + 6
m = -2/3
y - 4 = -2/3(x - 6)
3y - 12 = -2x + 12
2x + 3y - 24 = 0
We can multiply both the numerator and denominator by ANY number (as long as you multiply both the numerator and denominator by the SAME number) to get an equivalent fraction
examples would be 2/12 (numerator and denominator multiplied by 2)3/18 (by 3)
4/24 (by 4) etc.